2016
DOI: 10.1039/c6cp00382f
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for modulating the luminescence properties of pyronin Y dye–clay films: an experimental and theoretical study

Abstract: The aggregation process, particularly the type and extent of pyronin Y (PY) laser dye intercalated into supported thin films of two different trioctahedral clay minerals, LAPONITE® (Lap) and saponite (Sap), at different dye loadings is studied: (i) experimentally by means of electronic absorption and fluorescence spectroscopy and (ii) theoretically by modeling the distribution of the dye into the interlayer space of these layered silicates. According to the results, H-type aggregates of the PY dye are favoured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…Indeed inclusion compounds of engineered clays are beginning to show actual potential as eco‐friendly functional materials . Such progress was also fostered by modeling studies – that suggested, for example, to contrast the worsening in the mechanical properties of a clay (caused by the incorporation of dyes) via the co‐adsorption of surfactants in the interlayer space of the clay . Taking inspiration from Blue Maya, the indigo molecule was recently encapsulated into zeolite L microcrystals yielding an exceptionally robust colorant: the insight from simulations was instrumental for the successful blockage of the crystal terminations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed inclusion compounds of engineered clays are beginning to show actual potential as eco‐friendly functional materials . Such progress was also fostered by modeling studies – that suggested, for example, to contrast the worsening in the mechanical properties of a clay (caused by the incorporation of dyes) via the co‐adsorption of surfactants in the interlayer space of the clay . Taking inspiration from Blue Maya, the indigo molecule was recently encapsulated into zeolite L microcrystals yielding an exceptionally robust colorant: the insight from simulations was instrumental for the successful blockage of the crystal terminations.…”
Section: Discussionmentioning
confidence: 99%
“…[773][774][775][776][777][778] Such progress was also fostered by modeling studies -that suggested, for example, to contrast the worsening in the mechanical properties of a clay (caused by the incorporation of dyes) via the co-adsorption of surfactants in the interlayer space of the clay. [779][780][781] Taking inspiration from Blue Maya, the indigo molecule was recently encapsulated into zeolite L microcrystals yielding an exceptionally robust colorant: [782] the insight from simulations [191] was instrumental for the successful blockage of the crystal terminations. An atomistic knowledge of natural host matrices is also important for their use in environmental 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 protection (e. g., absorption of organic pollutants by layered hydroxides, [783,784] sequestration of trace uranium in multiphase iron minerals [785] ) and in the realization of new materials via sustainable fabrication approaches; for instance, using a vaporinduced approach, a direct synthesis of zeolites starting from clay minerals has been recently performed.…”
Section: Discussionmentioning
confidence: 99%
“…Saponite has a rigid structure and can provide a confined microenvironment to luminescent molecules on a nanoscale. Hence, in the interlayer space of Sap, J-aggregates with a more open geometry in which the luminescent dye molecules better contact with the surface of Sap become favorable (Epelde-Elezcano et al, 2016). A good dye distribution in the interlayer space of Sap can be achieved reducing molecular aggregation.…”
Section: Optical Materialsmentioning
confidence: 99%
“…These interactions are conducive to suppressing dye molecule aggregation. They can also increase luminous intensity of the dye molecules and extend the fluorescence lifetime Epelde-Elezcano et al, 2016;Boháč et l., 2016;Bujdák et al, 2016). In addition, in a confined microenvironment of the interlayer space of Sap, the dye molecules have to occur in a parallel orientation with respect to the surface of the Sap nanoparticles (Tominaga et al, 2017) (Fig.…”
Section: Optical Materialsmentioning
confidence: 99%
“…Among the clay minerals of interest is saponite, which has applications as: adsorbent for the removal of heavy metal ions [1,2] and carcinogenic compounds [3]; control agent of the aggregation of luminescent dyes [4,5]; matrix for controlled release of drugs [6]; catalysts for industrially important reactions [7][8][9] and for prebiotic chemistry [10,11] ; immobilization support for various catalysts [12][13][14][15] and many more. These applications would be dependent on properties such as size, cation-exchange capacity, plasticity, catalytic activity, swelling behavior, permeability, and substitutions in the saponite structure.…”
Section: Introductionmentioning
confidence: 99%